David Hume acerca del materialismo - Calvente, Sofía (Pontificia Universidad Católica del Perú, 2023)
During the 17th and 18th centuries, an intense debate concerning materialism took place. This paper aims to describe David Hume’s position within this debate. I claim that, even though Hume rejects substantialist metaphysics to focus on the study of perceptions, he defends a position concerning the relationship between mind and matter. However, this position is rather complex to reconstruct since it is not explicitly stated in the texts edited during Hume’s life. I propose to define it as a restricted materialism since, regarding the nature of mind, Hume discards both the materialist and the immaterialist positions; although concerning the causes of thought he comes close to materialist positions by using arguments based on experience and the analogy with nature.

Durante los siglos XVII y XVIII hubo un intenso debate en las Islas Británicas en torno al materialismo. Mi objetivo consiste en caracterizar la postura de David Hume en el marco de ese debate. Sostengo que, no obstante rechazar la metafísica sustancialista para centrarse en el estudio de las percepciones, Hume sienta una posición respecto de la relación entre mente y materia. Sin embargo, esa posición reviste cierta complejidad en tanto no es explicitada en los textos que se editaron en vida de Hume. Propongo definirla como un materialismo restringido, ya que, respecto de la naturaleza de la mente, Hume desestima tanto las posturas materialistas como inmaterialistas, pero respecto de las causas del pensamiento, termina acercándose al materialismo a partir de argumentos basados en la experiencia y en la analogía con la naturaleza.
David Hume on Materialism
Keywords: Mind; Matter; Substantialist metaphysics; Causality; Analogy with nature; Mente; Materia; Metafísica sustancialista; Causalidad; Analogía con la naturaleza; https://purl.org/pe-repo/ocde/ford#6.03.01